Cardiorespiratory effects of project energize: a whole-of region primary school nutrition and physical activity programme in New Zealand in 2011 and 2015 - Carolyn Cairncross; Victor Obolonkin; Tara Coppinger; Elaine Rush (BMC, 2020)
Abstract Background Since 2004, Sport Waikato has delivered Project Energize, a through-school nutrition and physical activity program to primary schools in the Waikato. As part of the program's continued assessment and quality control, the programme was evaluated in 2011 and 2015. This paper's aim was to compare the cardiorespiratory fitness (time to run 550 m (T550)) levels of children participating in Project Energize in 2011 and 2015. Methods In the 2011 evaluation of Project Energize, gender specific- T550-for-age Z scores (T550AZ) were derived from the T550 of 4832 Waikato children (2527 girls; 2305 boys; 36% Māori) aged between 6 and 12 years. In 2015, T550 was measured for 4798 (2361 girls; 2437 boys; 32% Māori) children, representative of age, gender and school socioeconomic status (SES). The T550AZ for every child in the 2015 study and 2011 evaluation were derived and differences in T550 between 2015 and 2011 by gender, SES and age were determined using independent t-tests. Multiple regression analysis predicted T550 Z score and run time, using year of measurement, gender, ethnicity, age and school SES. Results With and without adjustment, children in 2015 ran 550 m faster than in 2011 (adjusted Z score 0.06, time 11 s). Specifically, girls ran at a similar speed in 2015 as 2011 but boys were faster than in 2011 (Z score comparison P < 0.001, mean difference 0.18 95%CI 0.12, 0.25). Regression analysis showed time taken to run 550 m was 11 s less in 2015 compared with 2011. Boys ran it 13 s faster than girls (Z score 0.07) and for each 1 year age increase, children were 8 s slower (Z score 0.006). For each 10% decrease in SES, children were 3 s slower (Z score 0.004) and Māori children were 5 s slower than Non-Māori children (Z score 0.15). Conclusions The findings from this study support the continuation of the delivery of Project Energize in the Waikato region of New Zealand, as cardiorespiratory fitness scores in 2015, compared to 2011, were improved, particularly for lower SES schools and for Māori children. Ethnically diverse populations, schools with higher deprivation and girls, continue to warrant further attention to help achieve equity.